Geomorphic complexity influences coarse particulate organic matter transport and storage in headwater streams - Fogel, Caleb B.; Lininger, Katherine B. (Frontiers in Water, 2023)
Coarse particulate organic matter (CPOM; organic matter 1–100 mm in diameter, excluding small wood) stored in streams provides an important energy source for aquatic ecosystems, and CPOM transport provides downstream energy subsidies and is a pathway for watershed carbon export. However, we lack understanding of the magnitude of and processes influencing CPOM storage and transport in headwater streams. We assessed how geomorphic complexity and hydrologic regime influence CPOM transport and storage in the Colorado Front Range, USA. We compared CPOM transport during snowmelt in a stream reach with high retentive feature (e.g., wood, cobbles, and other features) frequency to a reach with low retentive feature frequency, assessing how within-a-reach geomorphic context influences CPOM transport. We also compared CPOM transport in reaches with differing valley geometry (two confined reaches versus a wide, multi-thread river bead) to assess the influence of geomorphic variations occurring over larger spatial extents. Additionally, we compared CPOM storage in accumulations in reaches (n = 14) with flowing water or dry conditions in late summer and investigated how small pieces of organic matter [e.g., woody CPOM and small wood (>1 min length and 0.05–1 min diameter or 0.5–1 min length and >0.1 min diameter)] influence CPOM storage. We found that within-a-reach retentive feature frequency did not influence CPOM transport. However, valley geometry influenced CPOM transport, with a higher CPOM transport rate (median: 1.53 g min−1) downstream of a confined stream reach and a lower CPOM transport rate (median: 0.13 g min−1) downstream of a low gradient, multi-thread river bead. Additionally, we found that particulate organic carbon (POC) export (0.063 Mg C) in the form of CPOM was substantially lower than dissolved organic carbon (DOC) export (12.3 Mg C) in one of these headwater streams during the 2022 water year. Dry reaches stored a higher volume of CPOM (mean = 29.18 m3 ha−1) compared to reaches with flowing water (15.75 m3 ha−1), and woody CPOM pieces trapped 37% of CPOM accumulations. Our results demonstrate that the influence of geomorphic context on CPOM transport depends on the scale and type of geomorphic complexity, POC may be lower than DOC export in some headwater streams, and small woody organic material is important for trapping CPOM small streams.